IMPLEMENTASI DATA MINING DALAM MENENTUKAN TATA LETAK PRODUK MENGGUNAKAN ALGORITMA FP-GROWTH - Prathama, Gede Humaswara; Devi Anggreni, Ni Komang Ayu; Oktavia Gama, Adie Wahyudi; Darma Paramartha, I Gusti Ngurah (Universitas Palangka Raya, 2025)
This study analyzes purchasing patterns in minimarkets using the FP-Growth algorithm to optimize product layouts. One year of sales transaction data (103,181 transactions) from UNDIKNAS Mart were analyzed through data cleaning, transformation, and aggregation. The FP-Growth algorithm was applied with minimum support 5%, confidence 80%, and lift >1 thresholds. Results identified strong product associations, particularly between